2015
DOI: 10.1158/1078-0432.ccr-14-2565
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Oral Cyclophosphamide and Veliparib in High-Grade Serous Ovarian, Primary Peritoneal, or Fallopian Tube Cancers, or BRCA-Mutant Ovarian Cancer

Abstract: Purpose Veliparib, a poly(ADP-ribose) polymerase (PARP) inhibitor, demonstrated clinical activity in combination with oral cyclophosphamide in patients with BRCA-mutant solid tumors in a phase 1 trial. To define the relative contribution of PARP inhibition to the observed clinical activity, we conducted a randomized phase 2 trial to determine the response rate of veliparib in combination with cyclophosphamide compared to cyclophosphamide alone in patients with pretreated BRCA-mutant ovarian cancer or in patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 41 publications
2
94
0
Order By: Relevance
“…Several PARP inhibitors are currently in development for the treatment of patients with tumors harboring HRD, including those with a BRCA1/2 mutation (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Single-agent olaparib is approved in the United States for the treatment of patients with advanced germline BRCA1/2-mutated ovarian cancer who have received three or more lines of chemotherapy (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…Several PARP inhibitors are currently in development for the treatment of patients with tumors harboring HRD, including those with a BRCA1/2 mutation (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Single-agent olaparib is approved in the United States for the treatment of patients with advanced germline BRCA1/2-mutated ovarian cancer who have received three or more lines of chemotherapy (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Kummar et al demonstrated in a small randomized trial of oral cyclophosphamide with or without velaparib (a PARP inhibitor) that low-dose cyclophosphamide is associated with responses and prolonged disease stabilization in pre-treated HGSOCs (11). There was a 19,4% (7/36 patients) overall response in the cyclophosphamide-only arm.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, PARP inhibitors have three main disadvantages. Firstly, recent studies demonstrated that HGSOCs become resistant to PARP inhibitors (11). Secondly, PARP inhibitors as well as bevacizumab combined with chemotherapy may cause significant side effects (15,16,19).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic sequence and expression analyses were performed for 211 genes involved in DNA repair; none of the detected genetic alterations were significantly associated with treatment benefit. It was well tolerated and clinical activity was observed; the addition of Veliparib at 60 mg daily did not improve either the response rate or the median progression-free survival [87].…”
Section: Veliparibmentioning
confidence: 97%